2019
DOI: 10.1083/jcb.201909137
|View full text |Cite
|
Sign up to set email alerts
|

C. elegans pronuclei fuse after fertilization through a novel membrane structure

Abstract: After fertilization, parental genomes are enclosed in two separate pronuclei. In Caenorhabditis elegans, and possibly other organisms, when the two pronuclei first meet, the parental genomes are separated by four pronuclear membranes. To understand how these membranes are breached to allow merging of parental genomes we used focused ion beam scanning electron microscopy (FIB-SEM) to study the architecture of the pronuclear membranes at nanometer-scale resolution. We find that at metaphase, the interface betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
52
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(54 citation statements)
references
References 50 publications
2
52
0
Order By: Relevance
“…Surprisingly, this phenotype persisted in the subsequent mitotic divisions during early embryogenesis [36]. More recent studies have demonstrated that wild-type Plk1 is required for the formation of a novel three-way membrane junction that promotes pronuclear fusion in C. elegans [37]. Interestingly, this structure does not normally form during subsequent somatic division in wild-type embryos, explaining the persistence of dual nuclei in temperature-sensitive plk1 mutants [37].…”
Section: Plos Geneticsmentioning
confidence: 97%
“…Surprisingly, this phenotype persisted in the subsequent mitotic divisions during early embryogenesis [36]. More recent studies have demonstrated that wild-type Plk1 is required for the formation of a novel three-way membrane junction that promotes pronuclear fusion in C. elegans [37]. Interestingly, this structure does not normally form during subsequent somatic division in wild-type embryos, explaining the persistence of dual nuclei in temperature-sensitive plk1 mutants [37].…”
Section: Plos Geneticsmentioning
confidence: 97%
“…To better understand how pronuclei fuse, in this issue, Rahman et al (7) used focused ion beam–scanning electron microscopy (FIB-SEM) in Caenorhabditis elegans zygotes, to study pronuclear fusion. The FIB-SEM approach allowed Rahman et al (7) to generate three-dimensional reconstructions of nuclear membranes from both wild-type and mutant embryos at prophase, prometaphase, and metaphase. These images confirmed early EM findings and revealed other novel observations leading to a new, multistep model for pronuclear fusion.…”
mentioning
confidence: 99%
“…Rahman et al (7) also examined pronuclear membranes in mutant embryos. It was previously shown that plk-1 is necessary for the mixture of parental genomes.…”
mentioning
confidence: 99%
See 2 more Smart Citations